Preterm prelabor rupture of membranes without microbial invasion of the amniotic cavity and intra-amniotic inflammation: a heterogeneous group with differences in adverse outcomes. (12th December 2022) - Kacerovsky, Marian; Matulova, Jana; Andrys, Ctirad; Mls, Jan; Hornychova, Helena; Kukla, Rudolf; Bostik, Pavel; Burckova, Hana; Spacek, Richard; Jacobsson, Bo; Musilova, Ivana
Abstract: Objective: The absence of microbial invasion of the amniotic cavity and intra-amniotic inflammation at the time of hospital admission is the most common condition associated with preterm prelabor rupture of membranes (PPROM). Although the intensity of intra-amniotic inflammatory response does not exceed the threshold for the diagnosis of intra-amniotic inflammation in this subgroup of PPROM, whether there could be differences in outcomes concerning the intensity of intra-amniotic inflammatory response remains unclear. Therefore, the main aims of this study on PPROM without microbial invasion of the amniotic cavity and intra-amniotic inflammation were (i) to characterize the association between the intensity of intra-amniotic inflammatory response, measured according to amniotic fluid interleukin (IL)-6 concentrations, and the presence of acute histological chorioamnionitis and acute inflammation in the amnion; (ii) to characterize the association between the intensity of intra-amniotic inflammatory response and fetal inflammatory response, and (iii) to describe the short-term morbidity of infants based on the intensity of intra-amniotic inflammatory response. Methods: This retrospective study included 131 women with singleton pregnancies with PPROM without microbial invasion of the amniotic cavity and intra-amniotic inflammation between gestational ages of 24 + 0 and 36 + 6 weeks and who had delivered within 72 h of membrane rupture. Microbial invasion of the amniotic cavity was assessed based on a combination of cultivation and non-cultivation methods. Intra-amniotic inflammation was characterized based on the amniotic fluid IL-6 concentration. In addition, a histopathological assessment of the placenta was performed. Fetal inflammatory response syndrome was characterized according to IL-6 concentration in the umbilical cord blood of >11 pg/mL. Based on the quartiles of IL-6 concentrations in the amniotic fluid, these women were divided into four subgroups (from the lowest to the highest IL-6 concentrations). Results: IL-6 concentrations in amniotic fluid were higher in women with acute histological chorioamnionitis (median: 819 pg/mL vs. 520 pg/mL; p = .003) and with acute inflammation of the amnion (median: 1116 pg/mL vs. 533 pg/mL; p = .0002) than in women without these complications. The rates of acute histological chorioamnionitis and acute inflammation of the amnion were the highest in the subgroup with IL-6 concentrations above the 75th percentile in amniotic fluid (chorioamnionitis, p = .02; amnion, p = .0002). No differences in IL-6 concentrations in amniotic fluid were identified between women with and without a fetal inflammatory response syndrome ( p = .40). The rate of fetal inflammatory response syndrome did not vary among the amniotic fluid IL-6 quartile subgroups of women. Moreover, no differences were noted in short-term neonatal outcomes among the amniotic fluid IL-6 quartile subgroups. Conclusion: A higher intensity of the intra-amniotic inflammatory response, measured by amniotic fluid IL-6 concentrations, is associated with a higher rate of acute inflammatory lesions in the placenta in the subset of PPROM pregnancies without microbial invasion of the amniotic cavity and intra-amniotic inflammation.